Comparison of outcomes between laparoscopic and open Hartmann's reversal: A single‐center retrospective study in Japan. Issue 1 (31st August 2021) - Sato, Aya; Imaizumi, Ken; Kasajima, Hiroyuki; Obuchi, Keisuke; Sato, Kentaro; Yamana, Daisuke; Tsuruga, Yosuke; Umehara, Minoru; Kurushima, Michihiro; Nakanishi, Kazuaki
Abstract: Introduction: Laparoscopic Hartmann's reversal (LHR) has recently been reported to be safer and more feasible than open Hartmann's reversal (OHR); however, there is limited data on the outcomes of LHR compared with those of OHR from Asian countries. Therefore, we aimed to clarify the postoperative outcomes of LHR compared with OHR, and additionally compare the patient outcomes post‐LHR according to the previous Hartmann's procedure (HP) approach. Methods: Patients who underwent OHR and LHR between January 2006 and September 2020 in a single center in Japan, were retrospectively evaluated. Patient characteristics and perioperative data were collected from the medical and surgical records and assessed. Results: Overall, 15 and 19 patients underwent OHR and LHR, respectively, between January 2006 and September 2020. LHR was associated with less blood loss (median: 15 mL vs 185 mL; P < .001) and shorter hospital stays (9 days vs 14 days; P = .023) than OHR. There was no significant difference in postoperative complications between LHR and OHR (26.3% vs 40.0%, P = .475). However, two severe anastomotic complications in LHR were observed in patients with the stump below the peritoneal reflection. No significant difference in outcomes was observed between LHR patients who underwent open and laparoscopic HP. Conclusion: LHR resulted in positive outcomes regarding estimated blood loss and postoperative hospitalization, compared with OHR. Although the postoperative complications between LHR and OHR were not significant, patients with the stump below the peritoneal reflection may be at a high risk of anastomotic complications.